Analisis Faktor Holland Career pada Ketertarikan Food Photography Unit Kegiatan Mahasiswa KOPPI (Komunitas Photography Pancasakti) di Masa Pandemi Covid-19 - Ayu Putri Chiisai; Choirunnisa Adinda Prihatin; Novi Mardiani Putri; Sesya Dias Mumpuni (Cakrawala: Jurnal Pendidikan, 2021)
The purpose of this study was to examine the influence of Holland Career on students of UKM KOPPI Tegal on the choice of the career based the type of personality expressed in the theory was in accordance with their study and activities of the photography students they were undergoing. The method used is quantitative pre-experimental, one shot case study design, used a Likert scale and data analysis with SPSS & manual calculations on the Pearson Product Moment Correlation. The use of the Jung Typology Test was carried out to obtain qualitative data as interpretation and observation of 15 respondents. The results showed that the Holland Career scale analysis test on Food Photography interest showed mostly invalid results, meaning that Holland Career scale analysis had no effect on interest Food Photography. However, the Jung Typology Test, which is part of the Holland Career test, shows a match in their study and shows a high percentage of their interest in food photography, which focuses on artistic, enterprising and conventional. The Holland Career has a significant effect on career choices in the their study and hobbies from the student activities they carry out, namely Photography.